2020
DOI: 10.1109/tcds.2019.2915763
|View full text |Cite
|
Sign up to set email alerts
|

Semantic Relational Object Tracking

Abstract: This paper addresses the topic of semantic world modeling by conjoining probabilistic reasoning and object anchoring. The proposed approach uses a so-called bottom-up object anchoring method that relies on rich continuous attribute values measured from perceptual sensor data. A novel anchoring matching function learns to maintain object entities in space and time and is validated using a large set of trained humanly annotated ground truth data of real-world objects. For more complex scenarios, a high-level pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 34 publications
1
30
0
Order By: Relevance
“…This inferred belief of the world is then sent back to the anchoring system, where the state of occluded objects is updated. The feedback-loop between the anchoring system and the probabilistic reasoner results in an additional anchoring functionality (Persson et al, 2020b):…”
Section: Requirements For Anchoring and Semantic Object Trackingmentioning
confidence: 99%
See 4 more Smart Citations
“…This inferred belief of the world is then sent back to the anchoring system, where the state of occluded objects is updated. The feedback-loop between the anchoring system and the probabilistic reasoner results in an additional anchoring functionality (Persson et al, 2020b):…”
Section: Requirements For Anchoring and Semantic Object Trackingmentioning
confidence: 99%
“…In Persson et al (2020b), we showed that enabling a perceptual anchoring system to reason further allows for correctly anchoring objects under object occlusions. We borrowed the idea of encoding a theory of occlusion as a probabilistic logic theory from Nitti et al (2014) (discussed in more detail in section 2.3).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations